Idiopathic Calcinosis Cutis over Elbow in a 12-Year Old Child - S. K. Venkatesh Gupta; Ramana Rao Balaga; Suman Kumar Banik (Case Reports in Orthopedics)
Calcinosis cutis is an uncommon disorder caused by an abnormal deposit of calcium phosphate in the skin in various parts of the body. Four main types of calcinosis cutis have been recognized according to etiology: associated with localized or widespread tissue changes or damage (dystrophic calcification), that associated with an abnormal calcium and phosphorus metabolism (metastatic calcification), not associated with any tissue damage or demonstrable metabolic disorder (idiopathic calcification), and Iatrogenic. Very few cases of idiopathic calcinosis cutis are reported in early childhood in the literature. We report one such case of idiopathic calcinosis cutis over elbow in a 12-year-old female child. Histological examinations of the lesions resected in this case reveal calcium deposits in the dermis, surrounded by foreign body giant cells. Idiopathic calcinosis cutis is a rare phenomenon and occurs in the absence of known tissue injury or systemic metabolic defect. It is important to delineate it from other calcification disorders for further plan of management. Medical therapy in calcinosis cutis is of limited benefit in pediatric age group and poses a challenging problem of postsurgical management.